Finding Dorothy : a novel - Letts, Elizabeth (Ballantine Books, 2019)
"This richly imagined novel tells the story behind The Wonderful Wizard of Oz, the book that inspired the iconic film, through the eyes of author L. Frank Baum's intrepid wife, Maud. Hollywood, 1938: As soon as she learns that M-G-M is adapting her late husband's masterpiece for the screen, seventy-seven-year-old Maud Gage Baum sets about trying to finagle her way onto the set. Nineteen years after Frank's passing, Maud is the only person who can help the producers stay true to the spirit of the book--because she's the only one left who knows its secrets. But the moment she hears Judy Garland rehearsing the first notes of "Over the Rainbow," Maud recognizes the yearning that defined her own life story: from her youth as a suffragette's daughter to her coming of age as one of the first women in the Ivy League, from her blossoming romance with Frank to the hardscrabble prairie years that inspired The Wonderful Wizard of Oz. Judy reminds Maud of a young girl she cared for and tried to help in South Dakota, a dreamer who never got her happy ending. Now, with the young actress under pressure from the studio as well as her ambitious stage mother, Maud resolves to protect her--the way she tried so hard to protect the real Dorothy"--